Peran Guru Dalam Membentuk Karakter Kedisiplinan Siswa Pai di Sekolah SMA IT Jabal Noor - Siregar, Rahma Yulia; P, Fuji Rahmadi (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the role of teachers in shaping the discipline character of Islamic Religious Education (PAI) students at SMA Jabal Noor. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with PAI teachers, students, and parents, as well as direct observations in classrooms and school environments. The results show that PAI teachers play an important role in shaping the discipline character of students through habituation and providing good examples. Additionally, PAI teachers also provide motivation and teaching based on Islamic values that emphasize the importance of discipline in everyday life. The formation of discipline is not limited to the school environment but extends to students' lives at home and in the community. Despite challenges, such as the negative influence of the external environment, the role of teachers remains significant in creating a supportive environment for shaping the students' discipline character. The recommendations from this study are the importance of cooperation between teachers, parents, and the community to support efforts in developing a better discipline character for students.